TRUST–POWER RELATIONSHIP AND TAX REPORTING BY PLATFORM WORKERS: A MODERATED MEDIATION MODEL - Nurshamimi Sabli; Anna Che Azmi; Noor Ismawati Jaafar (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
The power and trust relationship between tax authorities and taxpayers is thought to be important in shaping taxpayer compliance behaviour. Although a growing number of studies have considered moral and emotional elements in tax decision-making, the nexus between taxpayers’ honest intention and feelings of guilt towards their tax-reporting decision remains unclear. In support of studies on the digital or platform economy and the rising number of individuals earning income digitally, this study seeks to identify factors that influence individuals’ tax reporting decision of their digital income. Applying the Slippery Slope Framework, this study uses a 2 x 2 between-subjects factorial experimental design, in which the independent variables of this study, i.e., power and trust are manipulated. This study conducts a scenario-based experiment with eighty platform workers on an established digital platform. The findings reveal that high trust in authorities increases platform workers’ intention for honesty reporting and guilt for misreporting, promoting tax-reporting compliance. Moreover, this relationship is significantly moderated by the high-power condition. Specifically, it is believed that both enforcement and trust matter in achieving compliance in taxpayers’ reporting.